A contraction between Lie algebras with necessarily singular components of the contraction matrix - Popovych, D.R. (Reports of the National Academy of Sciences of Ukraine, 2014)
We present an example of a contraction between five-dimensional Lie algebras that is realized only with matrices, whose Euclidean norms necessarily approach infinity at the limit value of the contraction parameter. Dimension five is the lowest dimension of Lie algebras, between which contractions of the above kind exist.